Association between low dairy consumption and determinants of health in Latin American university students: a multicenter study - Gajardo González, Diego (2025)
Objective: to associate low dairy consumption with determinants of health and the Human Development Index (HDIs) in Latin American university students. Methods: a cross-sectional, multicenter, observational study in university students from eleven Latin American countries. Results: the study included 4880 subjects. In all, 66 % of the sample consumed at least one serving of dairy products per day. A higher percentage of dairy consumers was observed among participants who are in the highest quartile of quality of life as compared to those in the lowest quartile (p < 0.001). Dairy consumption was positively associated with the consumption of breakfast (OR, 1.58; 95 % CI, 1.36-1.85), healthy dinner (OR, 1.16; 95 % CI, 1.01-1.32), fruits (OR, 1.77; 95 % CI, 1.53-2.05), vegetables (OR, 1.19; 95 % CI, 1.02-1.39), fish (OR: 1.37; 95 % CI, 1.36-1.85), whole-grain foods (OR, 1.72; 95 % CI, 1.49-1.98), and the practice of physical activity (OR, 1.16; 95 % CI, 1.01-1.34), and was negatively associated with the consumption of fried food (non-consumption) (OR, 0.72; 95 % CI, 0.58-0.90), junk food (OR, 0.78; 95 % CI, 0.63-0.96), sweet snacks (OR, 0.69; 95 % CI, 0.57-0.82), and alcohol (OR, 0.83; 95 % CI, 0.72-0.95). Furthermore, to reside in a country whose HDI is medium-high was found to be associated as a risk factor for non-compliance with the recommended intake of at least 3 servings of dairy per day, as compared to individuals from countries with very high HDIs (OR, 2.05; 95 % CI, 1.79-2.36). In addition, the results show that being female is a protective factor and is associated with the compliance of the consumption recommendation for dairy products (OR, 0.83; 95 % CI, 0.71-0.98). Conclusion: dairy consumption is related to better diet quality and higher levels of physical activity. Complying with the recommendation to consume 3 servings of dairy per day is associated with better quality of diet, stressing the importance of promoting dairy consumption.